LEO THE HEBREW AND A KABBALISTIC READING OF PLATO’S TIMAEUS - Pinto de Brito, Rodrigo; Araújo Gomes, Gilmar (Prometheus - Journal of Philosophy., 2022)
This paper aims to consider the specific excerpts in which Plato’s Timaeus was interpreted by the philosopher and Kabbalist Judah Abravanel, also known as Leo the Hebrew in his major work, the Dialogues of Love. From his experience of solitude lived while in exile in Italy, the Portuguese Jew composes a work written in a structure of double meanings, esoteric and exoteric, through which he interacts with the Neoplatonic Renaissance community of his time while communicating with the Kabbalistic tradition from which he descended as a Sephardic. Interpreting Timaeus in the light of his ancestral cosmogony, Leo the Hebrew wants to prove that Plato was initiated into the teachings of Moses and, therefore, must be included as a Kabbalist.